Effectiveness of the physical activity promotion programme on the quality of life and the cardiopulmonary function for inactive people: Randomized controlled trial - Martín-Valero Rocío; Cuesta-Vargas Antonio Ignacio; Labajos-Manzanares María Teresa (BMC, 2013)
Abstract Background The purpose is to assess cardiopulmonary function outcomes and quality of life values in inactive people that participated in the Physical Activity Promotion Programme (PAPP) against the control group that did not perform this program. Method A total of 100 subjects of both genders participated in the randomized controlled trial with systematic random sampling; all were aged 55 and older, from Torremolinos, Spain. Participants either received (n = 50) the PAPP for 60 minutes, twice a week during three months or (n = 50) they received health education. The effectiveness of the intervention was measured by general state of health the Short Form 12 health survey questionnaire, and the quality of life was determined with the EuroQoL-5D questionnaire. Cardiopulmonary function was measured with a spirometry and a walking test according to the Bruce protocol. Results This pilot study had a significant impact on the quality of life (p = 0.05) in men, which increased. However, the quality of life in women did not improve. The average changes in the lung and cardiovascular function was not significant between groups. Conclusions Changes in the quality of life measured with EQ-5D in the group of men who carried out the PAPP were statistically significant when comparing between groups. However changes in cardiopulmonary function were not as relevant when comparing between groups. There was a significant effect within each group in the pulmonary outcomes of values in men, within the experimental group. Trial registration Developed by the University of Málaga. ClinicalTrials.gov ID: NCT01172483.